Synthesis and optimization of poly (HEMA-co-EGDMA-co-VBC) for preparation of hypercrosslinked aminated polymer using DoE method - Mohammad Zuhaili, Yahya (2017)
Hydrophilic quarternary ammonium resin (HQAR) was successfully derived from hypercrosslinked Poly(HEMA-co-EGDMA-co-VBC) polymer. The objective of this project is to develop HQAR via three stages, precursor synthesis (suspension polymerization), hypercrosslinking reaction, and functionalization reaction (amination). For first stage which suspension polymerization, several parameters were varied which were solvent mixture, solvent/porogen ratio, stirrer rotation, amount of initiator, amount of stabilizer, amount of crosslinker, amount of co-monomer and monomer concentration. To obtain highest quality particles, amount of crosslinker should being used at highest amount. Effect of crosslinker, co-monomer amount and monomer concentration were chosen for screening part using Design of Experiment (DoE) to study the interaction between these three factors. DoE analysis showed that the most significant factor was amount of crosslinker. Meanwhile, effects of crosslinker and co-monomer amount were chosen for DoE optimization part to optimize the particles for hypercrosslinking reaction. In second stage that involved hypercrosslinking reaction, the effect of crosslinker, co-monomer amount and catalyst ratio on particles specific surface area (SSA) were studied. Co-monomer and crosslinker amount to be significant parameters in order to obtain high SSA particles. Optimized precursors were chosen for optimization of hypercrosslinked polymer. In the last stage of this study, the optimized hypercrosslinked polymer was functionalized with Dimethylbutylamine (DMBA) to produce HQAR with positively charge group successfully attached to the backbone. The characterization involved in all stages were Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectrospcopy (FTIR), X-ray Flourescence (XRF), CHNS analysis, Brunauer-Emmet-Teller (BET) and Thermal Gravimetric Analysis (TGA).